The role of employee knowledge and behavior towards sustainable development: an investigative study based on readymade garments industry of Chittagong, Bangladesh - Islam, Ariful; Haja Maideen, Mazuwin; Abdullah, Abdul Rashid (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The sustainable development topic of readymade garments sector speaks to a flawed picture considering distinctive sustainable issues as ecological impressions, workplace or factory security and labor rights. Therefore, sustainable point of view mostly in the readymade garments industry has distinguished as a noteworthy subject because of upsurge responsiveness related with ecological and social impacts of concern industry mainly at developing countries such as Bangladesh. In fact the present authoritative culture of focused industry is kind of dynamic and complex where the complicacy of employee behavior and concerns connected with sustainable development issues that may deliver misconception in regards to how to approach employee contribution plans towards sustainable goals. Therefore the objective of present research is to recognize the level as well as the impact and relationship among employee knowledge and behavior of sustainable development in Chittagong, Bangladesh. The study has consumed mixed method approaches considering participants from BGMEA enlisted industries of Chittagong. The obtained outputs show that reflected participants hold moderate level of knowledge and behavior towards sustainable issues. It has also been identified that knowledge has significant impact on behavioral pattern of employees and both variables contain a positive connection. The acquired insights may encourage both employee and concern management to find the basic elements to start efficient association towards sustainable development practices.